Дополнительные возможности реализации инноваций в инженерном образовании - Назаренко, В. Г.; Орлов, М. А. (БНТУ, 2013)
We considered the sequence of training system for students and professionals in the field of intellectual property and its development. Also we proposed new opportunities for the development of a systematic approach to the development of creative solutions in engineering and education.
Additional possibilities of realization of innovations in engineering education